A teoria educacional e o edifício pedagógico - Silva, Renata Borges (2018)
In Brazil, the quality of teaching, in all its stages, has been questioned triggering many discussions, mainly in relation to the students' performance. These discussions have demonstrated the need to treat education and, consequently, educational building as a priority, since education is largely responsible for preparing individuals for life in society. The educational process, however, can not be separately evaluated. The educational building is the place where teaching and learning processes are developed and the relationship between pedagogy and architecture, especially with regard to early childhood education, should be explored. Interlocution between architecture and education can lead to a jump in quality and in children's school performance. For this reason, this theme becomes relevant. This dissertation aims to identify and prioritize which design elements can influence the relation between teaching and learning, acting as an integral part of the pedagogical methodology, highlighting how the building can contribute to the dynamics of children's knowledge, as well as to analyze which elements are capable of forming lasting affective ties, altering the meaning of the school, recoding its image to the little apprentice. It is also necessary to highlight different design elements, from schools of different pedagogical methodologies, evaluating the architectural choices relating them to the type of approach practiced; Therefore, as a working methodology, two schools are used as a case study, both aimed at early childhood education; the House of Letters (Casa das Letras) guided in the socio-interactionist pedagogy and the Creative Space (Espaço Criativo) directed by the humanistic pedagogy and constructivist partner, thus the teaching-learning relationship and building is observed.